Effect of Long-Term LMWH on Post-thrombotic Syndrome in Patients With Iliac/Noniliac Venous Thrombosis: A Subanalysis From the Home-LITE Study. (September 2013) - Hull, Russell D.; Liang, Jane; Merali, Tazmin
Patients with iliac deep vein thrombosis (DVT) have a poor prognosis and high incidence of postthrombotic syndrome (PTS). We evaluated the effect of low-molecular-weight heparin (LMWH; tinzaparin) versus usual care (tinzaparin plus warfarin for ≥12 weeks at home) in the development of PTS according to DVT location (iliac/noniliac) by retrospective analysis of the Home-LITE cohort (480 patients with proximal DVT). Patients with iliac DVT had an overall odds ratio of 0.53 (95% confidence interval [CI] 0.33, 0.83; P = .0079) for PTS (including ulcer data) in favor of tinzaparin. Patients with noniliac DVT had a similar odds ratio (0.79 [95% CI 0.67, 0.93], P = .0046) to that reported in the overall Home-LITE population (0.76 [95% CI 0.66, 0.89], P = .0004; including ulcer data), both in favor of tinzaparin. Long-term LMWH may be a suitable alternative for the prevention of PTS in patients with iliac DVT who are unlikely to undergo invasive thrombolysis.